Analisis Kinerja Aparatur Desa Majakerta Dalam Meningkatkan Kepuasan Masyarakat - Mustofa, Zaenal; Maryono, Dicky (STIM-LPI Makassar, 2025)
This study aims to analyze the performance of Majakerta Village officials in managing social assistance and its impact on community satisfaction. The method used was a qualitative approach through in-depth interviews with village officials, social assistance recipients, and community leaders. The results indicate that despite efforts in the distribution procedure, shortcomings remain, such as a lack of transparency and communication with the community. Community satisfaction is influenced by information transparency and speed of distribution. It is recommended that village officials increase outreach and implement a more transparent system in managing social assistance.